Sex ratio,gonad development and fecundity of Miyakella nepa(Crustacea, Stomatopoda) of Pantai Remis coastal waters of Malaysia - Zainudin, Zamri; Arshad, Aziz; Harmuj Ali Sarker, S. M. Nurul Amin; Rahman, Md. Aminur; Al Khayat, Jassim A. (Triveni Enterprises, 2016)
The sex ratio, gonad development and fecundity of Miyakella nepa (Latreille, 1828), in the coastal waters of Pantai Remis, Perak, were investigated from February 2012 to January 2013. Sex identification was done by identifying stomatopod's genitalia organs, and the ovaries were dissected out and preserved for further analysis. Female stomatopods with mature or near spawning stages were used for fecundity estimation. A total of 951 specimens of M. nepa, with 565 females and 386 males were examined. Results showed a sex ratio of 1:1.46 (male:females). Maximum GSI was estimated to be 5.80, while lowest was 2.95. Sexual maturity for female M. nepa was observed at 100 mm total length. The mean fecundity of M. nepa was 425,657 (± 1,8701) eggs which was observed to increase with increased body length.